Synthesis and Preclinical Evaluation of Small-Molecule Prostate-Specific Membrane Antigen-Targeted Abiraterone Conjugate - Machulkin, Aleksei E.; Nimenko, Ekaterina A.; Zyk, Nikolay U.; Uspenskaia, Anastasiia A.; Smirnova, Galina B.; Khan, Irina I.; Pokrovsky, Vadim S.; Vaneev, Alexander N.; Timoshenko, Roman V.; Mamed-Nabizade, Vugara V.; Zavertkina, Maria V.; Erofeev, Alexander; et al. (Molecules (Basel, Switzerland), 2022)
Prostate cancer is the second most common type of cancer among men. The main method of its treatment is androgen deprivation therapy, which has a wide range of side effects. One of the solutions to this challenge is the targeted delivery of drugs to prostate cancer cells. In this study, we performed the synthesis of a novel small-molecule PSMA-targeted conjugate based on abiraterone. Cytotoxicity, the induction of intracellular reactive oxygen species, and P450-cytochrome species inhibition were investigated for this conjugate PSMA-abiraterone. The conjugate demonstrated a preferential effect on prostate tumor cells, remaining inactive at up to 100 µM in human fibroblast cells. In addition, it revealed preferential efficacy, specifically on PSMA-expressing lines with a 65% tumor growth inhibition level on 22Rv1 (PSMA+) xenografts after 14-fold oral administration of PSMA-Abi at a single dose of 500 mg/kg (7.0 g/kg total dose) was observed. This compound showed significantly reduced acute toxicity with comparable efficacy compared to AbiAc.